The Land to Those Who Cultivate It? Collective Claims and Social Conflicts in Rural Spain from the late 19th Century to 1936 - Angelis-Dimakis, Dimitris (Mos Historicus: A Critical Review of European History, 2024)
The present study examines the course of collective mobilisations and social conflict in the Spanish countryside from the last decades of the nineteenth century until the beginning of the Spanish Civil War. It focuses on the social and political agents who established their own collective structures of a national scope, creating at the same time networks of local and regional organisations throughout the country. The article looks into the evolution of the collective demands with particular emphasis on the views expressed regarding the thorny issue of land redistribution and the prospect of land reform. Thus, it sheds light on the character and the dynamics of social tensions in the Spanish rural societies, tracing continuities and discontinuities, peaks and troughs.